"Housing Prices Never Fall": The Development of Housing Finance in Taiwan. Issue 4 (3rd July 2020) - Chen, Yi-Ling
ABSTRACT: This article deals with the path-dependent features of financialization of housing in Taiwan, an East Asian developmental state. The levels of foreign capital and securitization in Taiwan's housing market remain relatively low, meaning domestic capital, of which there is an abundance, is the major financial source of such speculation. The process does not include the retrenchment of the welfare state, because Taiwan has been a homeowner society. After financial liberalization in the 1980s, Taiwan's state intervention in the housing and financial sectors has actually intensified via the enactment of more regulations to decrease the role of the informal financial and housing sectors. As a result of neoliberalization giving precedence to market mechanisms, various low-interest mortgage programs in the 1990s, all subsidized by public funding, have increased the rate of homeownership and sustained housing prices. Even though this varied the development of housing financialization, housing in Taiwan has largely become a tool of speculation, and housing affordability has become a serious problem.